New treatments in renal cancer: The AhR ligands - Itkin, Boris (2020)
Kidney cancer rapidly acquires resistance to antiangiogenic agents, such as sunitinib, developing an aggressive migratory phenotype (facilitated by c-Metsignal transduction). The Aryl hydrocarbon receptor (AhR) has recently been postulated as a molecular target for cancer treatment. Currently, there are two antitumor agent AhR ligands, with activity against renal cancer, that have been tested clinically: aminoflavone (AFP 464, NSC710464) and the benzothiazole (5F 203) prodrug Phortress. Our studies investigated the action of AFP 464, the aminoflavone pro-drug currently used in clinical trials, and 5F 203 on renal cancer cells, specifically examining their effects on cell cycle progression, apoptosis and cell migration. Both compounds caused cell cycle arrest and apoptosis but only 5F 203 potently inhibited the migration of TK-10, Caki-1 and SN12C cells as well as the migration signal transduction cascade, involving c-Met signaling, in TK-10 cells. Current investigations are focused on the development of nano-delivery vehicles, apoferritin-encapsulated benzothiazoles 5F 203 and GW610, for the treatment of renal cancer. These compounds have shown improved antitumor effects against TK-10 cells in vitro at lower concentrations compared with a naked agent.